Led Astray by Hemoglobin A1c - Jean Chen MD; Amy Diesburg-Stanwood DN; Geza Bodor MD; Neda Rasouli MD (SAGE Publishing, 2016)
Hemoglobin A1c (A1c) is used frequently to diagnose and treat diabetes mellitus. Therefore, it is important be aware of factors that may interfere with the accuracy of A1c measurements. This is a case of a rare hemoglobin variant that falsely elevated a nondiabetic patient's A1c level and led to a misdiagnosis of diabetes. A 67-year-old male presented to endocrine clinic for further management after he was diagnosed with diabetes based on an elevated A1c of 10.7%, which is approximately equivalent to an average blood glucose of 260 mg/dL. Multiple repeat A1c levels remained >10%, but his home fasting and random glucose monitoring ranged from 92 to 130 mg/dL. Hemoglobin electrophoresis and subsequent genetic analysis diagnosed the patient with hemoglobin Wayne, a rare hemoglobin variant. This variant falsely elevates A1c levels when A1c is measured using cation-exchange high-performance liquid chromatography. When the boronate affinity method was applied instead, the patient's A1c level was actually 4.7%. Though hemoglobin Wayne is clinically silent, this patient was erroneously diagnosed with diabetes and started on an antiglycemic medication. Due to this misdiagnosis, the patient was at risk of escalation in his "diabetes management" and hypoglycemia. Therefore, it is important that providers are aware of factors that may result in hemoglobin A1c inaccuracy including hemoglobin variants.